Bulk composition and clay mineralogy at DSDP Legs 56 and 57 - Ulrich Mann; German Müller (PANGAEA, 1980)
Altogether 513 samples from sediments of Cretaceous to Pleistocene age from DSDP Legs 56 and 57 were examined by x-ray methods. The main constituents are clay minerals, quartz, feldspar, opaline silica, and volcanic glass. The sediment composition reflects the position of the sites in relation to the main source area, the Japanese Island Arc. For example, relatively coarse-grained material rich in quartz and feldspar was deposited closest to the islands, whereas finer-grained material rich in clay minerals (mainly smectite and illite, with lesser amounts of kaolinite and chlorite) was deposited farther seaward. Vertical fluctuations in the composition of the sediments show the same trend in all sites and are caused mainly by a fluctuating contribution of biogenic silica with time. A trend reversal in the chlorite/kaolinite ratio at Site 438 supports the conclusion that the subsidence of the Oyashio ancient landmass took place during the middle Miocene. That ratio also indicates a northwest drift in the position of Site 436 by sea floor spreading. Oscillations of the illite/smectite ratio during the Pleistocene at Site 436 show the variations of climate during this period. During early diagenesis potassium is fixed in smectite. With increasing depth of burial a smectite-illite mixed layer is formed, with increasing illite layering. At Sites 434, 440, and 441, stepwise changes confirm intensive tectonic process at the midslope terrace and the lower inner slope of the Japan Trench.
Supplement to: Mann, U; Müller, G (1980): Composition of sediments of the Japan Trench transect, Legs 56 and 57, Deep Sea Drilling Project. In: Scientific Party, Initial Reports of the Deep Sea Drilling Project, 56/57 (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 56-57, 939-977, https://doi.org/10.2973/dsdp.proc.5657.133.1980